Menstrual Stem cells - Shuchi Lakhanpal; Bindiya Gupta (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Stem cells isolated from menstrual fluid have mesenchymal stem cell like properties and have multi lineage differentiation capacity. Menstrual fluid has ease of access in collection and repeated sampling is possible in a noninvasive manner. Also, rapid culture of these is possible in numbers that are sufficient for therapeutic use. They are, hence, looked upon as a novel innovation and are finding a place in the current medicine practice